Nurturing Growth: Exploring Factors Influencing Female Youth Entrepreneurs in Lusaka's Central Business District (Global Journal of Management and Business Research, 2024)
Female youth entrepreneurship is increasingly acknowledged as a catalyst for economic growth productivity innovation and job creation It plays a pivotal role in sustaining economic dynamism and competitiveness on the global stage In contributing to the corpus of literature on female entrepreneurship this study analyzed factors influencing the performance of female youth entrepreneurs in small and medium enterprises SMEs in Lusaka Zambia The research employed an explanatory mixed methods design and used structured interviews and purposive sampling to collect data The research findings indicate a commendable pattern of adherence to local authority requirements with 72 majority of female entrepreneurs having consistently fulfilled their tax and levy obligations to the local authority On marketing strategy the study has shown that most female entrepreneurs use social media platforms such Facebook as their core marketing channel The study revealed the intricate challenges that female youth entrepreneurs face when striving to balance the demands of their businesses with family and personal responsibilities To address challenges faced by female entrepreneurs the study recommends the need to implement and expand financial programs that specifically target female entrepreneurs
Keywords: employment; economic growth; entrepreneur-ship